Impacts of Fertilization Optimization on Soil Nitrogen Cycling and Wheat Nitrogen Utilization Under Water-Saving Irrigation - Zhang, Zhen; Yu, Zhenwen; Zhang, Yongli; Shi, Yu (Frontiers in Plant Science, 2022)
Scholars have proposed the practice of split nitrogen fertilizer application (SNFA), which has proven to be an effective approach for enhancing nitrogen use efficiency. However, the combined effects of SNFA on wheat plant nitrogen use efficiency, ammonia (NH3) emission flux, as well as the rates of nitrification and denitrification in different ecosystems remain unclear. Meanwhile, few studies have sought to understand the effects of the split nitrogen fertilizer method under water-saving irrigation technology conditions on nitrogen loss. The current study assessed soil NH3 volatilization, nitrification and denitrification intensities, as well as the abundance of nitrogen cycle-related functional genes following application of different treatments. Specifically, we applied a nitrogen rate of 240 kg·ha-1, and the following fertilizer ratios of the percent base to that of topdressing under water-saving irrigation: N1 (basal/dressing, 100%/0%), N2 (basal/dressing, 70%/30%), N3 (basal/dressing, 50%/50%), N4 (basal/dressing, 30%/70%), and N5 (basal/dressing, 0%/100%). N3 treatment significantly reduced NH3 volatilization, nitrification and denitrification intensities, primarily owing to the reduced reaction substrate concentration (NO3- and NH4+) and abundance of functional genes involved in the nitrogen cycle (amoA-AOB, nirK and nirS) within the wheat-land soil. 15N tracer studies further demonstrated that N3 treatments significantly increased the grain nitrogen accumulation by 9.50%-28.27% compared with that under other treatments. This increase was primarily due to an increase in the amount of nitrogen absorbed by wheat from soil and fertilizers, which was caused by an enhancement in total nitrogen uptake (7.2%-21.81%). Overall, N3 treatment (basal/dressing, 50%/50%) was found to effectively reduce nitrogen loss through NH3 volatilization, nitrification and denitrification while improving nitrogen uptake by wheat. Thus, its application will serve to further maximize the yield and provide a fertilization practice that will facilitate cleaner wheat production in the North China Plain.